The E3 Ubiquitin Ligase TRIM65 Negatively Regulates Inflammasome Activation Through Promoting Ubiquitination of NLRP3 - Tang, Tiantian; Li, Ping; Zhou, Xinhui; Wang, Rui; Fan, Xiuqin; Yang, Mengyi; Qi, Kemin (Frontiers in Immunology, 2021)
The dysregulation of NLRP3 inflammasome plays a critical role in pathogenesis of various human inflammatory diseases, thus NLRP3 inflammasome activation must be tightly controlled at multiple levels. However, the underlying mechanism regulating NLRP3 inflammasome activation remains unclear. Herein, the effects of Tripartite motif-containing protein 65 (TRIM65) on NLRP3 inflammasome activation and the underlying molecular mechanism were investigated in vitro and in vivo. Inhibition or deletion of Trim65 could significantly strengthened agonists induced NLRP3 inflammasome activation in THP-1 cells and BMDMs, indicated by increased caspase-1 activation and interleukin-1β secretion. However, TRIM65 had no effect on poly (dA: dT)-induced AIM2 inflammasome activation or flagellin-induced IPAF inflammasome activation. Mechanistically, immunoprecipitation assays demonstrated that TRIM65 binds to NACHT domain of NLRP3, promotes lys48- and lys63- linked ubiquitination of NLRP3 and restrains the NEK7-NLRP3 interaction, thereby inhibiting NLRP3 inflammasome assembly, caspase-1 activation, and IL-1β secretion. In vivo, three models of inflammatory diseases were used to confirm the suppression role of TRIM65 in NLRP3 inflammasome activation. TRIM65-deficient mice had a higher production of IL-1β induced by lipopolysaccharide in sera, and more IL-1β secretion and neutrophil migration in the ascites, and more severity of joint swelling and associated IL-1β production induced by monosodium urate, suggesting that TRIM65 deficiency was susceptible to inflammation. Therefore, the data elucidate a TRIM65-dependent negative regulation mechanism of NLRP3 inflammasome activation and provide potential therapeutic strategies for the treatment of NLRP3 inflammasome-related diseases.